Well-being of international project assignees on international project assignments : In the context of a case organization - Mikkola, Ellen (My University, 2025)
In today’s global world international work is a norm. Different types of international work have become more common in recent years. This research focused on international project assignments. During the latest years the importance of well-being has continued to increase. The aim of this study was to define what affected the international project assignee's well-being on international project assignments in the context of the case organization. Moreover, this study focused on factors that decrease and factors that increase project assignee’s well-being on international project assignments in the context of the case organization. The theo-retical framework of this study was grounded in the Job Demands–Resources Theory which provided a way to examine how various job demands and resources affected international project assignee well-being. This study was conducted as qualitative research by interviewing international project assign-ees from the chosen case organization. Twelve international project assignees were inter-viewed for the purposes of this study. The participants all spent a significant amount of time per year on international project assignments. The interviews were one on one interviews. All the interviews were conducted online between December 2024 and January 2025. All inter-views were recorded and transcript. Most of the interviews were hold in Finnish and some in English. The analysis of the data was done by using the interpretative phenomenological analysis (IPA) method which allowed the analysis to focus on the individual’s own interpretations of their well-being. The findings of the study demonstrated how social support, organizational sup-port, personal resources, free time, experience and contact with family increased internation-al project assignee well-being on international project assignments in the context of the case organization. Pressure, communications issues, lack of routine, challenges in adapting to a new culture, health and safety concerns and feelings of stress and uncertainty on the other hand decreased international project assignee well-being on international project assign-ments in the context of the case organization. This study also included suggestions for the case organization to further help in the process of improving their international project assignee well-being on international project assign-ments. It would be very beneficial for the case organization to take certain actions such as providing better accommodation, offering and providing even more support and hearing and taking the international project assignees’ thoughts and opinions into account even more.

Nykyisessä globalisoituneessa maailmassa kansainvälinen työskentely on muodostunut nor-miksi. Erilaiset kansainvälisen työn muodot ovat yleistyneet merkittävästi viime vuosina. Tämä tutkimus keskittyi erityisesti kansainvälisiin projektikomennuksiin. Viime vuosina työntekijöi-den hyvinvoinnin merkitys on kasvanut huomattavasti. Tämän tutkimuksen tavoitteena oli selvittää, mitkä tekijät vaikuttavat kansainvälisten projektikomennuslaisten hyvinvointiin kan-sainvälisillä projektikomennuksilla kohdeorganisaation kontekstissa. Tarkoituksena oli tunnis-taa, mitkä tekijät heikensivät ja mitkä tekijät edistivät heidän hyvinvointiaan. Tutkimuksen teoreettinen viitekehys pohjautui työn vaatimusten ja voimavarojen teoriaan (Job Demands–Resources Theory), joka tarjosi viitekehyksen työssä esiintyvien vaatimusten ja voimavarojen vaikutusten tarkasteluun hyvinvoinnin näkökulmasta. Tutkimus toteutettiin laadullisena tutkimuksena, jossa aineisto kerättiin haastattelemalla kan-sainvälisiä projektikomennuslaisia valitusta kohdeorganisaatiossa. Tutkimukseen osallistui kaksitoista kansainvälistä projektikomennuslaista, jotka kaikki viettivät merkittävän osan vuo-desta ulkomailla kansainvälisillä projektikomennuksilla. Haastattelut toteutettiin yksilöhaastat-teluina, ja ne suoritettiin etäyhteyksin joulukuun 2024 ja tammikuun 2025 välisenä aikana. Kaikki haastattelut nauhoitettiin ja litteroitiin analysointia varten. Suurin osa haastatteluista pidettiin suomen kielellä, mutta osa pidettiin myös englanniksi. Aineiston analyysissä hyödynnettiin tulkitsevaa fenomenologista analyysimenetelmää (In-terpretative Phenomenological Analysis, IPA), jonka avulla voitiin syventyä yksilöiden omiin kokemuksiin ja tulkintoihin tekijöistä, jotka vaikuttivat heidän omaan hyvinvointiinsa kansain-välisillä projektikomennuksilla. Tutkimuksen tulokset osoittivat, että sosiaalinen ja organisaa-tion tuki, henkilökohtaiset voimavarat, vapaa-aika, aiempi kokemus sekä yhteydenpito per-heeseen lisäsivät kansainvälisten projektikomennuslaisten hyvinvointia. Sen sijaan paine, vies-tinnän haasteet, rutiinien puute, vaikeudet uuden kulttuurin omaksumisessa, terveys- ja tur-vallisuushuolenaiheet sekä stressin ja epävarmuuden kokemukset heikensivät haastateltavien hyvinvointia kansainvälisillä projektikomennuksilla. Tämä tutkimus tarjoaa kohdeorganisaatiolle myös käytännön suosituksia, joiden avulla kan-sainvälisten projektikomennuslaisten hyvinvointia voidaan parantaa. Esimerkiksi paremmat majoitusjärjestelyt, tuen lisääminen sekä työntekijöiden kokemusten ja mielipiteiden aktiivi-sempi huomioiminen voisivat edistää hyvinvointia merkittävästi.
Keywords: well-being; projects; well-being at work; working abroad; assignment; project work; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Henkilöstöjohtamisen maisteriohjelma|en=Master's Programme in Human Resource Management|